Queering Translation, Translating the Queer Theory, Practice, Activism - Baer, Brian James; Kaindl, Klaus (Routledge Advances in Translation and Interpreting Studies, 2018)
This groundbreaking work is the first full book-length publication to critically engage in the emerging field of research on the queer aspects of translation and interpreting studies. The volume presents a variety of theoretical and disciplinary perspectives through fifteen contributions from both established and up-and-coming scholars in the field to demonstrate the interconnectedness between translation and queer aspects of sex, gender, and identity. The book begins with the editors' introduction to the state of the field, providing an overview of both current and developing lines of research, and builds on this foundation to look at this research more closely, grouped around three different sections: Queer Theorizing of Translation; Case Studies of Queer Translations and Translators; and Queer Activism and Translation. This interdisciplinary approach seeks to not only shed light on this promising field of research but also to promote cross fertilization between these disciplines towards further exploring the intersections between queer studies and translation studies, making this volume key reading for students and scholars interested in translation studies, queer studies, politics, and activism, and gender and sexuality studies.